Applicability and performance of EUCAST’s rapid antimicrobial susceptibility testing (RAST) on primarily sterile body fluids in blood culture bottles in laboratory routine with total lab automation - Jasuja, Jasmin Kaur; Zimmermann, Stefan; Burckhardt, Irene (European journal of clinical microbiology & infectious diseases, 2021)
Optimisation of microbiological diagnostics in primarily sterile body fluids is required. Our objective was to apply EUCAST’s RAST on primarily sterile body fluids in blood culture bottles with total lab automation (TLA) and to compare results to our reference method Vitek2 in order to report susceptibility results earlier. Positive blood culture bottles (BACTEC™ Aerobic/ Anaerobic/PEDS) inoculated with primarily sterile body fluids were semi-automatically subcultured onto Columbia 5% SB agar, chocolate agar, MacConkey agar, Schaedler/KV agar and Mueller-Hinton agar. On latter, cefoxitin, ampicillin, vancomycin, piperacillin/tazobactam, meropenem and ciprofloxacin were added. After 6 h, subcultures and RAST were imaged and MALDITOF MS was performed. Zone sizes were digitally measured and interpreted following RAST breakpoints for blood cultures. MIC values were determined using Vitek2 panels. During a 1-year period, 197 Staphylococcus aureus, 91 Enterococcus spp., 38 Escherichia coli, 11 Klebsiella pneumoniae and 8 Pseudomonas aeruginosa were found. Categorical agreement between RAST and MIC was 96.5%. Comparison showed no very major errors, 2/7 (28.6%) and 1/7 (14.3%) of major errors for P. aeruginosa and meropenem and ciprofloxacin, 1/9 (11.1%) for K. pneumoniae and ciprofloxacin, 4/69 (7.0%) and 3/43 (5.8%) for Enterococcus spp. and vancomycin and ampicillin, respectively. Minor errors for P. aeruginosa and meropenem (1/8; 12.8%) and for E. coli and ciprofloxacin (2/29; 6.5%) were found. 30/550 RAST measurements were within area of technical uncertainty. RAST is applicable and performs well for primarily sterile body fluids in blood culture bottles, partially better than blood-based RAST. Official EUCAST evaluation is needed.
Gesehen am 24.07.2023